A Study of Morbidity and Mortality Profile in General Population of Hosangabad District (Madhya Pradesh) - Sanjay Kumar Gupta; Atul Varshney; Saurabh Sharma; Manish Dwivedi; Sunil Nandeshwar; Rakesh Kakkar (Medsci Publications, 2012)
Objective: The study was conducted to estimate the morbidity and mortality status of general population in the Hoshangabad District. Methodology: This is a community-based cross-sectional (descriptive) study carried out in the Hosangabad district of Madhya Pradesh covering of 509 families comprises of 2985 population. Sample was selected by multistage sampling technique. Result - A total of 2985 respondents, 725 (24%) were from Rural areas and 2260 (76%) from Urban areas. Major cause 640 (21%) of morbidity were due to acute illnesses. In acute illnesses most common was Acute Respiratory Infection241 (8.07%) followed by worm infection 84 (2.81%) and gastroenteritis 58(1.94%). Prevalence of ARI was higher in rural areas but gastroenteritis was higher in urban areas. Most common cause of chronic morbidity among studied population was cataract 42 (1.37%) followed by arthritis 24 (0.80%) and chronic amoebiasis 21 (0.70%). Acute morbidity in urban areas was higher in females (20%) than males (15%). Age specific mortality rate for age group 0-1 and 46-60 & above were significantly higher in rural areas than urban areas. Mortality rate were higher in females (9.7/1000) than males (7.2/1000). Most common cause of mortality in rural areas were diarrhoea, vomiting and dehydration (DVD) 7(38%) followed by cardiac diseases 3(17%) and in contrast urban areas were cardiac diseases 3(43%) followed by 1 (14%) DVD.